Antecedents and outcomes of the knowledge management process (KMP) in Malaysian SMEs - Narayanan, Sivachandran; Nadarajah, Devika; Sambasivan, Murali; Ho, Jo Ann (Taylor and Francis Group, 2020)
The purpose of this research was to identify and validate the antecedents and outcomes of the Knowledge Management Process (KMP) in the context of Malaysian SMEs. The antecedents (knowledge management (KM) enablers) in this study were internal collaboration, trust, small and medium enterprise (SME) network, transformational leadership, and information technology (IT) support. The outcomes were innovation speed and organizational performance. Data was collected from 242 SMEs through online surveys and personal visits and analyzed using partial least squares structural equation modeling (PLS-SEM).The salient findings were: (1) among the KM enablers, internal collaboration and IT support significantly influence the KMP; and (2) innovation speed mediates the relationship between the KMP and organizational performance. This study contributes to the literature by: (1) providing a comprehensive framework that links KM enablers, KMP, and performance for SMEs; and (2) establishing innovation speed as a mediator between the KMP and performance.